Beyond Inclusion: Explaining China's Rejection on the Indo-Pacific Regional Construct - Jaknanihan, Arrizal Anugerah (UI Scholars Hub, 2022)
The concept of “Indo-Pacific” has been increasingly adopted in foreign policies during the past few years. Despite its multifaceted nature, China has consistently rejected the use of the Indo-Pacific concept in its official policy. Beijing’s attitude was reflected in Chinese Foreign Minister Wang Yi’s remarks that dismissed the Indo-Pacific as a “come-back of Cold War mentality” and “retrogression of history.” This study explains why China renounced the Indo-Pacific concept despite the increasing inclusion in defining the region. By employing realist constructivism theory, this paper finds that the prevalence of containment and anti-China narrative engenders Beijing’s threat perception to the concept. The dominant narratives in China’s regional strategy, such as “community of common destiny,” also affect how the country treats the Indo-Pacific as a Western-centric concept, aimed to limit China’s influence. Beyond seeking inclusion from the Indo-Pacific conception, China advances its own vision to the region. China’s vision is projected through the Belt and Road Initiatives and various concepts to shape regional order in Beijing's preference.